Sosialisasi Penerapan Pendidikan Karakter Dan Kearifan Lokal Di Sekolah Dasar Negeri 54/IV Kecamatan Danau Teluk Kota Jambi - A A Musyaffa; Siti Asiah; Siti Ubaidah; Rapiko Rapiko; Umil Muhsinin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Elementary school students need to get character education strengthening through education in everyday life so they are able to practice character values, namely nationalist, religious, mutual cooperation, independence, and integrity values. There are phenomena that arise related to character violations which are quite worrying, for example acts of violence, violations of human rights (HAM), free sex, indiscipline, anarchism, corruption, theft, dishonesty, and so on. For this reason, we need a solution, one of which is strengthening character education based on local wisdom culture which is carried out in stages through socialization where the students are. Character education with local wisdom has a role as a driving force that carries good rules and norms to be practiced in everyday life. This activity was carried out at SD Negeri 54/IV, Danau Teluk District for 2 days, namely 2-28 May 2022 and continued with activities, with participants totaling 40 students. The results of the socialization of this activity indicate an increase in insight and understanding of character education and recognition of one's own potential in instilling local wisdom and training the spirit of leadership. This can be seen from the activeness and high enthusiasm of the participants for two days with a usefulness level of 3.75 on average, in addition to positive support from the principal and teaching staff being an important element of this activity. As well as in the learning process there is an influence, namely in cycle 1 the average student score is 67 and after cycle 2 it increases to 78 with improvements to the methods and media used during the learning process in accordance with the school environment and local environment.